Fullerenol-cytotoxic conjugates for cancer chemotherapy - Chaudhuri, Padmaparna; Paraskar, Abhimanyu; Soni, Shivani; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (ACS Nano, 2009)
In the present study, we report the novel application of polyhydroxylated fullerenes (fullerenols) in cancer drug delivery. The facile synthetic procedure for generating multiple hydroxyl groups on the fullerene cage offers scope for high drug loading in addition to conferring hydrophilicity. Doxorubicin, a first line cancer chemotherapeutic, was conjugated to fullerenols through a carbamate linker, achieving ultrahigh loading efficiency. The drug-fullerenol conjugate was found to be relatively stable in phosphate buffer saline but temporally released the active drug when incubated with tumor cell lysate. The fullerenol-doxorubicin conjugate suppressed the proliferation of cancer cell-lines in vitro through a G2-M cell cycle block, resulting in apoptosis. Furthermore, in an in vivo murine tumor model, fullerenol-doxorubicin exhibited Comparable antitumor efficacy as free drug without the systemic toxicity of free doxorubicin. Additionally, we demonstrate that the fullerenol platform can be extended to other chemotherapeutic agents, such as the slightly water-soluble cisplatin, and can emerge as a new paradigm in the management of cancer.
Keywords: chemotherapy; doxorubicin; drug delivery; fullerenol; nanoparticle

Nanoparticle-mediated targeting of MAPK signaling predisposes tumor to chemotherapy - Basu, Sudipta; Harfouche, Rania; Soni, Shivani; Chimote, Geetanjali; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2009)
The MAPK signal transduction cascade is dysregulated in a majority of human tumors. Here we report that a nanoparticle-mediated targeting of this pathway can optimize cancer chemotherapy. We engineered nanoparticles from a unique hexadentate-polyD, L-lactic acid-co-glycolic acid polymer chemically conjugated to PD98059, a selective MAPK inhibitor. The nanoparticles are taken up by cancer cells through endocytosis and demonstrate sustained release of the active agent, resulting in the inhibition of phosphorylation of downstream extracellular signal regulated kinase. We demonstrate that nanoparticle-mediated targeting of MAPK inhibits the proliferation of melanoma and lung carcinoma cells and induces apoptosis in vitro. Administration of the PD98059-nanoparticles in melanoma-bearing mice inhibits tumor growth and enhances the antitumor efficacy of cisplatin chemotherapy. Our study shows the nanoparticle-mediated delivery of signal transduction inhibitors can emerge as a unique paradigm in cancer chemotherapy.
Keywords: cancer; Signal transduction

Coupling growth-factor engineering with nanotechnology for therapeutic angiogenesis - Roy, Rituparna Sinha; Soni, Shivani; Harfouche, Rania; Vasudevan, Pooja R.; Holmes, Oliver; de Jonge, Hugo; Rowe, Arthur; Paraskar, Abhimanyu; Hentschel, Dirk M.; Chirgadze, Dimitri; Blundell, Tom L.; Gherardi, Ermanno; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Therapeutic angiogenesis is an emerging paradigm for the management of ischemic pathologies. Proangiogenic Therapy is limited, however, by the current inability to deliver angiogenic factors in a sustained manner at the site of pathology. In this study, we investigated a unique nonglycosylated active fragment of hepatocyte growth factor/scatter factor, 1K1, which acts as a potent angiogenic agent in vitro and in a zebrafish embryo and a murine matrigel implant model. Furthermore, we demonstrate that nanoformulating 1K1 for sustained release temporally alters downstream signaling through the mitogen activated protein kinase pathway, and amplifies the angiogenic outcome. Merging protein engineering and nanotechnology offers exciting possibilities for the treatment of ischemic disease, and furthermore allows the selective targeting of downstream signaling pathways, which translates into discrete phenotypes.
Keywords: cardiovascular disease; HGF/SF; ischemic disease; nanoparticle; protein engineering

Harnessing structure-activity relationship to engineer a cisplatin nanoparticle for enhanced antitumor efficacy - Paraskar, Abhimanyu S.; Soni, Shivani; Chin, Kenneth T.; Chaudhuri, Padmaparna; Muto, Katherine W.; Berkowitz, Julia; Handlogten, Michael W.; Alves, Nathan J.; Bilgicer, Basar; Dinulescu, Daniela M.; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cisplatin is a first line chemotherapy for most types of cancer. However, its use is dose-limited due to severe nephrotoxicity. Here we report the rational engineering of a novel nanoplatinate inspired by the mechanisms underlying cisplatin bioactivation. We engineered a novel polymer, glucosamine-functionalized polyisobutylene-maleic acid, where platinum (Pt) can be complexed to the monomeric units using a monocarboxylato and an O –> Pt coordinate bond. We show that at a unique platinum to polymer ratio, this complex self-assembles into a nanoparticle, which releases cisplatin in a pH-dependent manner. The nanoparticles are rapidly internalized into the endolysosomal compartment of cancer cells, and exhibit an IC50 (4.25 + 0.16 mu M) comparable to that of free cisplatin (3.87 +/- 0.37 mu M), and superior to carboplatin (14.75 +/- 0.38 mu M). The nanoparticles exhibited significantly improved antitumor efficacy in terms of tumor growth delay in breast and lung cancers and tumor regression in a K-ras(LSL/+)/Pten(fl/fl) ovarian cancer model. Furthermore, the nanoparticle treatment resulted in reduced systemic and nephrotoxicity, validated by decreased biodistribution of platinum to the kidney as quantified using inductively coupled plasma spectroscopy. Given the universal need for a better platinate, we anticipate this coupling of nanotechnology and structure-activity relationship to rationally reengineer cisplatin could have a major impact globally in the clinical treatment of cancer.
Keywords: cancer; chemotherapy; nanomedicine

Cholesterol-tethered platinum II-based supramolecular nanoparticle increases antitumor efficacy and reduces nephrotoxicity - Sengupta, Poulomi; Basu, Sudipta; Soni, Shivani; Pandey, Ambarish; Roy, Bhaskar; Oh, Michael S.; Chin, Kenneth T.; Paraskar, Abhimanyu S.; Sarangi, Sasmit; Connor, Yamicia; Sabbisetti, Venkata S.; Kopparam, Jawahar; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Nanoscale drug delivery vehicles have been harnessed extensively as carriers for cancer chemotherapeutics. However, traditional pharmaceutical approaches for nanoformulation have been a challenge with molecules that exhibit incompatible physicochemical properties, such as platinum-based chemotherapeutics. Here we propose a paradigm based on rational design of active molecules that facilitate supramolecular assembly in the nanoscale dimension. Using cisplatin as a template, we describe the synthesis of a unique platinum (II) tethered to a cholesterol backbone via a unique monocarboxylato and O -> Pt coordination environment that facilitates nanoparticle assembly with a fixed ratio of phosphatidylcholine and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine- N-[amino (polyethylene glycol)-2000]. The nanoparticles formed exhibit lower IC50 values compared with carboplatin or cisplatin in vitro, and are active in cisplatin-resistant conditions. Additionally, the nanoparticles exhibit significantly enhanced in vivo antitumor efficacy in murine 4T1 breast cancer and in K-Ras(LSL/+/)Pten(fl/fl) ovarian cancer models with decreased systemic- and nephro-toxicity. Our results indicate that integrating rational drug design and supramolecular nanochemistry can emerge as a powerful strategy for drug development. Furthermore, given that platinum-based chemotherapeutics form the frontline therapy for a broad range of cancers, the increased efficacy and toxicity profile indicate the constructed nanostructure could translate into a nextgeneration platinum-based agent in the clinics.
Keywords: chemotherapy; nanomedicine

Supramolecular nanoparticles that target phosphoinositide-3-kinase overcome insulin resistance and exert pronounced antitumor efficacy - Kulkarni, Ashish A.; Roy, Bhaskar; Rao, Poornima S.; Wyant, Gregory A.; Mahmoud, Ayaat; Ramachandran, Madhumitha; Sengupta, Poulomi; Goldman, Aaron; Kotamraju, Venkata Ramana; Basu, Sudipta; Mashelkar, Raghunath Anant; Ruoslahti, Erkki; et al. (Cancer Research, 2013)
The centrality of phosphoinositide-3-kinase (PI3K) in cancer etiology is well established, but clinical translation of PI3K inhibitors has been limited by feedback signaling, suboptimal intratumoral concentration, and an insulin resistance ``class effect.'' This study was designed to explore the use of supramolecular nanochemistry for targeting PI3K to enhance antitumor efficacy and potentially overcome these limitations. PI3K inhibitor structures were rationally modified using a cholesterol-based derivative, facilitating supramolecular nanoassembly with L-alpha-phosphatidylcholine and DSPE-PEG [1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino(polythylen e glycol)]. The supramolecular nanoparticles (SNP) that were assembled were physicochemically characterized and functionally evaluated in vitro. Antitumor efficacy was quantified in vivo using 4T1 breast cancer and K-Ras(LSL/+)/Pten(fl/fl) ovarian cancer models, with effects on glucose homeostasis evaluated using an insulin sensitivity test. The use of PI103 and PI828 as surrogate molecules to engineer the SNPs highlighted the need to keep design principles in perspective; specifically, potency of the active molecule and the linker chemistry were critical principles for efficacy, similar to antibody-drug conjugates. We found that the SNPs exerted a temporally sustained inhibition of phosphorylation of Akt, mTOR, S6K, and 4EBP in vivo. These effects were associated with increased antitumor efficacy and survival as compared with PI103 and PI828. Efficacy was further increased by decorating the nanoparticle surface with tumor-homing peptides. Notably, the use of SNPs abrogated the insulin resistance that has been associated widely with other PI3K inhibitors. This study provides a preclinical foundation for the use of supramolecular nanochemistry to overcome current challenges associated with PI3K inhibitors, offering a paradigm for extension to other molecularly targeted therapeutics being explored for cancer treatment. (C)2013 AACR.

Role of structure and entropy in determining differences in dynamics for glass formers with different interaction potentials - Banerjee, Atreyee; Sengupta, Shiladitya; Sastry, Srikanth; Bhattacharyya, Sarika Maitra (Physical Review Letters, 2014)
We present a study of two model liquids with different interaction potentials, exhibiting similar structure but significantly different dynamics at low temperatures. By evaluating the configurational entropy, we show that the differences in the dynamics of these systems can be understood in terms of their thermodynamic differences. Analyzing their structure, we demonstrate that differences in pair correlation functions between the two systems, through their contribution to the entropy, dominate the differences in their dynamics, and indeed overestimate the differences. Including the contribution of higher order structural correlations to the entropy leads to smaller estimates for the relaxation times, as well as smaller differences between the two studied systems.

Unraveling the success and failure of mode coupling theory from consideration of entropy - Nandi, Manoj Kumar; Banerjee, Atreyee; Sengupta, Shiladitya; Sastry, Srikanth; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2015)
We analyze the dynamics of model supercooled liquids in a temperature regime where predictions of mode coupling theory (MCT) are known to be valid qualitatively. In this regime, the Adam-Gibbs (AG) relation, based on an activation picture of dynamics, also describes the dynamics satisfactorily, and we explore the mutual consistency and interrelation of these descriptions. Although entropy and dynamics are related via phenomenological theories, the connection between MCT and entropy has not been argued for. In this work, we explore this connection and provide a microscopic derivation of the phenomenological Rosenfeld theory. At low temperatures, the overlap between the MCT power law regime and AG relation implies that the AG relation predicts an avoided divergence at T-c, the origin of which can be related to the vanishing of pair configurational entropy, which we find occurring at the same temperature. We also show that the residual multiparticle entropy plays an important role in describing the relaxation time. (C) 2015 AIP Publishing LLC.

Reporter nanoparticle that monitors its anticancer efficacy in real time - Kulkarni, Ashish; Rao, Poornima; Natarajan, Siva; Goldman, Aaron; Sabbisetti, Venkata S.; Khater, Yashika; Korimerla, Navya; Chandrasekar, Vineethkrishna; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The ability to monitor the efficacy of an anticancer treatment in real time can have a critical effect on the outcome. Currently, clinical readouts of efficacy rely on indirect or anatomic measurements, which occur over prolonged time scales postchemotherapy or postimmunotherapy and may not be concordant with the actual effect. Here we describe the biology-inspired engineering of a simple 2-in-1 reporter nanoparticle that not only delivers a cytotoxic or an immunotherapy payload to the tumor but also reports back on the efficacy in real time. The reporter nanoparticles are engineered from a novel two-staged stimuli-responsive polymeric material with an optimal ratio of an enzyme-cleavable drug or immunotherapy (effector elements) and a drug function-activatable reporter element. The spatiotemporally constrained delivery of the effector and the reporter elements in a single nanoparticle produces maximum signal enhancement due to the availability of the reporter element in the same cell as the drug, thereby effectively capturing the temporal apoptosis process. Using chemotherapy-sensitive and chemotherapy-resistant tumors in vivo, we show that the reporter nanoparticles can provide a real-time noninvasive readout of tumor response to chemotherapy. The reporter nanoparticle can also monitor the efficacy of immune checkpoint inhibition in melanoma. The self-reporting capability, for the first time to our knowledge, captures an anticancer nanoparticle in action in vivo.
Keywords: chemotherapy; immunotherapy; monitoring; nanoparticle; reporter

Unbiased phenotype-based screen identifies therapeutic agents selective for metastatic prostate cancer - Chung, Ivy; Zhou, Kun; Barrows, Courtney; Banyard, Jacqueline; Wilson, Arianne; Rummel, Nathan; Mizokami, Atsushi; Basu, Sudipta; Sengupta, Poulomi; Shaikh, Badaruddin; Sengupta, Shiladitya; Bielenberg, Diane R.; et al. (Frontiers in Oncology, 2021)
In American men, prostate cancer is the second leading cause of cancer-related death. Dissemination of prostate cancer cells to distant organs significantly worsens patients' prognosis, and currently there are no effective treatment options that can cure advanced-stage prostate cancer. In an effort to identify compounds selective for metastatic prostate cancer cells over benign prostate cancer cells or normal prostate epithelial cells, we applied a phenotype-based in vitro drug screening method utilizing multiple prostate cancer cell lines to test 1,120 different compounds from a commercial drug library. Top drug candidates were then examined in multiple mouse xenograft models including subcutaneous tumor growth, experimental lung metastasis, and experimental bone metastasis assays. A subset of compounds including fenbendazole, fluspirilene, clofazimine, niclosamide, and suloctidil showed preferential cytotoxicity and apoptosis towards metastatic prostate cancer cells in vitro and in vivo. The bioavailability of the most discerning agents, especially fenbendazole and albendazole, was improved by formulating as micelles or nanoparticles. The enhanced forms of fenbendazole and albendazole significantly prolonged survival in mice bearing metastases, and albendazole-treated mice displayed significantly longer median survival times than paclitaxel-treated mice. Importantly, these drugs effectively targeted taxane-resistant tumors and bone metastases - two common clinical conditions in patients with aggressive prostate cancer. In summary, we find that metastatic prostate tumor cells differ from benign prostate tumor cells in their sensitivity to certain drug classes. Taken together, our results strongly suggest that albendazole, an anthelmintic medication, may represent a potential adjuvant or neoadjuvant to standard therapy in the treatment of disseminated prostate cancer.
Keywords: bone; carcinoma; drug-screen; Metastasis; Prostate

Thermodynamics and its correlation with dynamics in a mean-field model and pinned systems: a comparative study using two different methods of entropy calculation - Nandi, Ujjwal Kumar; Patel, Palak; Moid, Mohd; Nandi, Manoj Kumar; Sengupta, Shiladitya; Karmakar, Smarajit; Maiti, Prabal K.; Dasgupta, Chandan; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2022)
A recent study introduced a novel mean-field model system where each particle over and above the interaction with its regular neighbors interacts with k extra pseudo-neighbors. Here, we present an extensive study of thermodynamics and its correlation with the dynamics of this system. We surprisingly find that the well-known thermodynamic integration (TI) method of calculating the entropy provides unphysical results. It predicts vanishing of the configurational entropy at temperatures close to the onset temperature of the system and negative values of the configurational entropy at lower temperatures. Interestingly, well below the temperature at which the configurational entropy vanishes, both the collective and the single-particle dynamics of the system show complete relaxation. Negative values of the configurational entropy are unphysical, and complete relaxation when the configurational entropy is zero violates the prediction of the random first-order transition theory (RFOT). However, the entropy calculated using the two-phase thermodynamics (2PT) method remains positive at all temperatures for which we can equilibrate the system, and its values are consistent with RFOT predictions. We find that with an increase in k, the difference in the entropy computed using the two methods increases. A similar effect is also observed for a system where a randomly selected fraction of the particles are pinned in their positions in the equilibrated liquid. We show that the difference in entropy calculated via the 2PT and TI methods increases with pinning density.

architecturally rational hemostat for rapid stopping of massive bleeding on anticoagulation therapy - Lee, Vivian K.; Lee, Taewoo; Ghosh, Amrit; Saha, Tanmoy; Bais, V. Manish; Bharani, Kala Kumar; Chag, Milan; Parikh, Keyur; Bhatt, Parloop; Namgung, Bumseok; Venkataramanan, Geethapriya; Agrawal, Animesh; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Hemostatic devices are critical for managing emergent severe bleeding. With the increased use of anticoagulant therapy, there is a need for next- generation hemostats. We rationalized that a hemostat with an architecture designed to increase contact with blood, and engineered from a material that activates a distinct and undrugged coagulation pathway can address the emerging need. Inspired by lung alveolar architecture, here, we describe the engineering of a next- generation single - phase chitosan hemostat with a tortuous spherical microporous design that enables rapid blood absorption and concentrated platelets and fibrin microthrombi in localized regions, a phenomenon less observed with other classical hemostats without structural optimization. The interaction between blood components and the porous hemostat was further amplified based on the charged surface of chitosan. Contrary to the dogma that chitosan does not directly affect physiological clotting mechanism, the hemostat induced coagulation via a direct activation of platelet Toll - like receptor 2. Our engineered porous hemostat effectively stopped the bleeding from murine liver wounds, swine liver and carotid artery injuries, and the human radial artery puncture site within a few minutes with significantly reduced blood loss, even under the anticoagulant treatment. The integration of engineering design principles with an understanding of the molecular mechanisms can lead to hemostats with improved functions to address emerging medical needs.
Keywords: biomaterial; clotting; hemostasis; hemostat; trauma